As transformações do modelo de desenvolvimento e a internacionalização do capital produtivo chinês - Mescollotto, Karina (2018)
This dissertation brings a study about the determinants of the chinese productive capital internationalization, on the period of 2006 to 2015, and the importance of the State and its industrial policy in this process. China has been adopting a differentiated industrial policy in comparison to the developed countries. This policy is bringing positive output into the economic and structural sphere of the country, influencing China‘s enterprises internationalization too. Furthermore, China has stood out because of the non-traditional approach it has used to internationalize its enterprises, the system of comparative disadvantages, which has brought positive returns to the economy and development of the country. Hereby, this dissertation shows the fundamental role of the State in the economic development of China. Finally, there is the intention to analyze, through an empirical approach, to which countries the chinese investment is directed, to which kind of sectors and for what purpose. This will be based on Dunning‘s eclectic paradigm. The results were like expected. There‘s more chance of China investing in countries with higher GDPs and strategic assets indicators, like United Stated, Japan and Germany, and natural resource indicators, like United States, Brazil and Australia, with the purposes of market-seeking, strategic asset-seeking and resource-seeking, respectively.